Reconstruction of Indonesian Tax Law Based on The Principle Of Distributive Justice To Establish A Welfare State In The Framework of The Rule of Law - Pamungkas, Ery; Samosir, Tetti; Munzil, Fontian; Hidayati, Maslihati Nur (Journal of Law, Politic and Humanities, 2025)
Amidst efforts to establish a welfare state, the current tax system actually creates economic injustice through the dominance of regressive indirect taxes, asymmetric law enforcement, and a transparency deficit that weakens public legitimacy. This study uses a dogmatic research method and deeply analyzes the vertical and horizontal consistency between legal norms and tax practices. The study was conducted using a textual and conceptual approach, as well as an assessment of the harmonization of various related regulations. The results show a disharmony between the constitutional mandate demanding distributive justice and consumption tax policies and weak enforcement against corporate tax avoidance. This phenomenon is exacerbated by limited transparency and accountability in the use of tax funds, leading to a crisis of public trust. The paper recommends a comprehensive reconstruction of the tax system, including strengthening progressive taxation, equal law enforcement, increasing fiscal transparency, harmonizing regulations, and adopting international practices, so that the tax system can function optimally as an instrument for redistributing welfare in accordance with the principles of the Pancasila rule of law.